KETAHANAN MASYARAKAT PESISIR KECAMATAN KAMPUNG LAUT DALAM MENGHADAPI PENYUSUTAN LAGUNA SEGARA ANAKAN - Rahmayana, Lintang; Handayani, Wiwandari (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2019)
The existence of Segara Anakan Lagoon increasingly getting worse. The amount of sedimentation rate makes the lagoon has height sediment. In addition the environmental degradation that happen caused by community activity, this can make worsening the situation. Â This study aims to assess the resilience capacity index of lagoon community in Kampung Laut Sub-district towards the decline of lagoon area. The variables used in this study are economic, human, social, physical and ecological. The five variables have indicators that can represent the resilience if lagoon community in Kampung Laut sub-district. Â Based on the results of the analysis conducted, it can be seen that the resilience index of the Kampung Laut community is in the medium category with a index of 0.52. However, if this assess more deeply, the resilience of Kampung Laut community might occur because the external factor more dominating than internal factors. This situation makes the Kampung Laut community resilience pretending to have enough resistance than the real condition. Behind this condition, it makes the community dependent on assistance from external parties, so the Kampung Laut community resilience gained not because they are empowered but there are other factors that influence it.